THE EFFECTIVENESS OF USING BOARD GAMES TO IMPROVE EIGHTH GRADE STUDENTS’ SPEAKING FLUENCY: EFEKTIVITAS PENGGUNAAN BOARD GAMES UNTUK MENINGKATKAN FLUENSI BERBICARA SISWA KELAS VIII - Ningsih, Tanti Fitria; Widhiatama, Daniel Ari (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
Speaking is the most important skill to acquire when learning a language. In fact, fluency is recognized as the natural ability to speak arguably spontaneously, quickly, and thoroughly when accuracy focuses on the phonological, grammatical, and discourse elements of speech output. The work is about improving her 8th grade fluency through the use of board games at SMP Al Ma’arif Bantul. The purpose of this study was to determine whether board games were effective in improving her 8th grade fluency. The study design used is based on quantitative quasi-experimental studies. Based on research results analyzed in SPSS 21, the result showed the different significance before and after treatment with data analysis criteria of t-test that H0 (null hypothesis) was rejected and Ha (alternative hypothesis) was accepted if the value was probably (p) lower than alpha (<) 0,05. The conclusion of the study showed the effectiveness of using Board Game for speaking fluency